STUDI TENTANG ANAK YANG KURANG PERCAYA DIRI PADA PESERTA DIDIK DI SMA NEGERI 05 PONTIANAK - Yossi Erma Yolanda; Luhur Wicaksono; Yuline Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractSelf confidence was a positive attitude of an individual to develop positive, good judgment about himself and to the enviroment/situation it faces. This research background was there were students who lack confidence in learning process shown by students who were afraid and nervous to argue in front of the class. There’s also the purpose of this research to see the characteristics of students who lack confidence, the factors and the impact of students who were less confident, and BK teachers’ efforts in dealing with students who were less confident in SMAN 05 Pontianak. This subjects in this study were three students. This research using descriptive qualitative. Data collection techniques used questionnaires and interviews. Based on the results, the characteristics of children who lack self-confidence were shy, indifferent, insecure, and quiet. Factors that students lack confidence because stress factors in the family, away from parents, and bullying. Impact that students who lack confidence, they only have a few friend, ignored by other friends, and depending on one freind close only. And action of BK teacher’s was asked the parents of the students who had lack confidence to come to the school.Keywords:Lack of Confidence, Students